Responses of Coral-Associated Bacterial Communities to Local and Global Stressors - McDevitt-Irwin, Jamie M.; Baum, Julia K.; Garren, Melissa; Vega Thurber, Rebecca L. (Frontiers in Marine Science, 2017)
The microbial contribution to ecological resilience is still largely overlooked in coral reef ecology. Coral-associated bacteria serve a wide variety of functional roles with reference to the coral host, and thus, the composition of the overall microbiome community can strongly influence coral health and survival. Here, we synthesize the findings of recent studies (n=45) that evaluated the impacts of the top three stressors facing coral reefs, climate change, water pollution and overfishing, on coral microbiome community structure and diversity. Contrary to the species losses that are typical of many ecological communities under stress, here we show that microbial richness tends to be higher rather than lower for stressed corals (i.e. in ~60% of cases), regardless of the stressor. Microbial responses to stress were taxonomically consistent across stressors, with specific taxa typically increasing in abundance (e.g. Vibrionales, Flavobacteriales, Rhodobacterales, Altermonadales, Rhizobiales, Rhodospirillales and Desulfovibrionales) and others declining (e.g. Oceanosprillales). Emerging evidence also suggests that stress may increase the microbial beta diversity amongst coral colonies, potentially reflecting a reduced ability of the coral host to regulate its microbiome. Moving forward, studies will need to discern the implications of stress-induced shifts in microbiome diversity for the coral hosts and may be able to use microbiome community structure to identify resilient corals. The evidence we present here supports the hypothesis that microbial communities play important roles in ecological resilience, and we encourage a focus on the microbial contributions to resilience for future research.